Subtilis, inutilis: the Jesuit pedagogy of ingenuity at La Flèche in the seventeenth century - Garrod, R (Springer, 2022)
Using the spider emblem of the ingenium from Antoine de Bourgogne’s Mundi lapis lydius (Compass of the World, 1639) as its pretext, this chapter explores the Jesuit pedagogy of ingenuity at La Flèche in the seventeenth century. It makes sense of this image and its motto by exploring the ways in which ingenuity was represented, assessed, and managed in the manuals of rhetoric, poetics, logic, natural philosophy and mixed mathematics which feature in the La Flèche historical library.